Experimental of Seawater Desalination Using Thermosolar Energy - Margarita Castillo Téllez, Beatriz Castillo Téllez; Chan González, Jorge de Jesús; Sarracino, Omar Martínez (European Journal of Sustainable Development, 2018)
Desalination of seawater or brackish water is a proven technology for more than 50 years which provides fresh water to millions of people living in areas of water scarcity, whether for drinking or other uses, such as hygiene and even agricultural, helping these communities not only to survive, but to achieve their economic, technological and environmental development. Unfortunately, current commercial desalination requires a large amount of energy, either caloric or electric and mostly covered by conventional sources, increasing both costs and environmental pollution. Freezing desalination can theoretically achieve up to 70 % less energy use than thermal technologies, with other advantages such as that it does not need pre-treatment and low corrosion in the system. The present work shows the results obtained during the experimentation in a prototype of desalination plant of sea water by freezing, coupled to a solar cooling system, managing to increase water production for each energy unit used and it is presented an analysis of salt percent obtained in water produced.